KEEFEKTIFAN METODE ROLE PLAY TERHADAP NILAI MORAL ANAK USIA 5-6 TAHUN - Nurhayati Nurhayati; Sita Awalunisah; Amrullah Amrullah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The role play method has become one of the most popular teaching methods for children. The purpose of using this method is to stimulate children's development, one of which is to develop children's moral values. Moral values ​​are very important in human life because of that, it needs to be planted since early childhood. However, most teachers use conventional methods to teach so that this method is less applied as a teaching method, especially in schools that are more academic. This article presents a teaching method using the role play method to stimulate children's moral values. The study design used a quasi-experimental pretest-posttest non equivalent control group design. Data collection used observation and compared with the -t test in the experimental group and the control group. The results show that effective role play methods are applied as children's learning methods to stimulate the moral value of early childhood.